Exploring the Impact of Organizational Culture, Mutation, and Career Development on Employee Performance: A Case Study of the West Java Water Resources Office - Puspaati, Ratih; Mulyana, Deden; Badruzaman, Jajang (The International Journal of Business Review (The Jobs Review), 2023)
The purpose of this study was to describe and analyze the influence of organizational culture, transfers, and career development on employee performance. The research method used is the census method with a quantitative approach. The research sample was 101 respondents, namely employees at the Department of Water and Mineral Resources of West Java Province with the saturated sampling method, which provided the opportunity for all members of the population to act as samples. Data were collected through observation techniques and questionnaires. The data analysis technique used is path analysis technique. The results showed that organizational culture, transfer and career development had an effect on performance either partially or simultaneously.